Social Security and Poverty Alleviation during the Covid-19 Pandemic: A Case Study in Pekalongan, Central Java, Indonesia - M. Yulian Akbar; Hartuti Purnaweni (Budapest International Research and Critics University, 2021)
In Covid-19 pandemic, poverty rate is getting worse. To tackle this condition, the government made comprehensive programs to help the poor. However, the problems arise as whether the implementation of poverty reduction policies during the Covid-19 pandemic is in accordance with the established rules and how the level of vulnerability of the poor whose scope is increasingly widespread. This study aims to explore what factors influence poverty during the Covid-19 pandemic in Pekalongan Regency and the role of social security program to alleviate poverty duting the pandemic. More specifically, this study aims to analyze the factors that influence poverty during the Covid-19 pandemic. The research is conducted in Pekalongan Regency with the aim of analyzing the factors that influence the increase in poverty in Pekalongan Regency. The results of the study show the factors of vulnerability, accessibility, termination of employment, and the narrowness of doing business due to social curbs for the poor. Meanwhile, factors from the local government were also found, namely the limited budget for poverty alleviation and the not yet optimal policies implemented.